Acute Posterior Multifocal Placoid Pigment Epitheliopathy Associated with Gastrointestinal Stromal Tumor and Hurthle Cell Tumor - Daniel D. Kim; Ghassan Ghorayeb (Case Reports in Ophthalmological Medicine)
Acute posterior multifocal placoid pigment epitheliopathy (APMPEE) is a chorioretinal inflammatory disease of unknown origin. Patients usually present with a rapid loss of central/paracentral vision over the course of a week in both eyes. The fundus exhibits rapid appearance of multiple deep subretinal yellow-white, flat lesions at the RPE/choriocapillaris level. This in turn causes changes of both the ellipsoid zone and RPE which can result in permanent central vision loss. The pathogenesis is controversial but is associated with a recent viral illness and can involve the central nervous system with concern for cerebral vasculitis. Rare reports of APMPEE associated with systemic vasculitis such as Wegener’s granulomatosis and malignancy such as clear cell renal carcinoma have been reported. We report a case of APMPEE with concurrent diagnosis of gastrointestinal stromal tumor and Hurthle cell tumor. While such association may well be coincidental, the near simultaneous presentation raised our suspicion for potential association.